IMPLEMENTATION OF ONLINE LEARNING MODELS FOR EFFECTIVE LEARNING RECOMMENDATIONS IN NEW NORMAL TIME - Erlyna Tri Rohmiatun; Wahyu Maulida Lestari (Sean Institute, 2022)
he application of social distancing as the main factor for the new normal creates its own challenges for the world of education, which is usually a face-to-face meeting between teachers/lecturers and their students/students in a pleasant atmosphere turning into online learning. Education must be implemented in the implementation of the teaching and learning process in the new era Normal activities can still be carried out without reducing the meaning of learning and ignoring the role of the teacher/lecturer as a teacher. Based on these problems, the online learning model is the main recommendation in learning. The purpose of this study was to determine and analyze the use of learning models in improving student learning outcomes in the new normal. This research uses qualitative analysis. The research was conducted on campus with the research subjects of lecturers and students. Data collection tools using questionnaires, research data were analyzed using descriptive analysis. In this study, it was concluded that lecturers must make and implement new breakthroughs in the form of online learning models during lectures in the current new normal, one of which is by implementing lecture methods that will lead to increasing online learning comfort and critical thinking of a student. So it is hoped that students can be comfortable and follow the lectures well even though online lectures are carried out. In this study, it was concluded that lecturers must make and implement new breakthroughs in the form of online learning models during lectures in the current new normal, one of which is by implementing lecture methods that will lead to increasing online learning comfort and critical thinking of a student. So it is hoped that students can be comfortable and follow the lectures well even though online lectures are carried out. In this study, it was concluded that lecturers must make and implement new breakthroughs in the form of online learning models during lectures in the current new normal, one of which is by implementing lecture methods that will lead to increasing online learning comfort and critical thinking of a student. So it is hoped that students can be comfortable and follow the lectures well even though online lectures are carried out.